1979
DOI: 10.1073/pnas.76.9.4511
|View full text |Cite
|
Sign up to set email alerts
|

Murine erythroleukemia cell differentiation: relationship of globin gene expression and of prolongation of G1 to inducer effects during G1/early S.

Abstract: Murine erythroleukemia cells (MELC) are induced to erythroid differentiation by culture with 4 mM hexamethylenebisacetamide. The relationship between onset of accumulation of globin mRNA and cell cycle phase has been examined in MELC fractionated with respect to cell cycle (GI, (1). The cellular and molecular target(s) of inducer effect on MELC have yet to be elucidated although data have been adduced to support putative targets at the plasma membrane (2, 3) as well as at nuclear (chromatin) sites (4-6). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Commitment has been thought to be limited to a specific phase of the cell cycle (4,6,18). Herbimycin-treated TSA8 cells can pass through one S phase but are arrested at the Gi phase and at the G2/M boundary (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Commitment has been thought to be limited to a specific phase of the cell cycle (4,6,18). Herbimycin-treated TSA8 cells can pass through one S phase but are arrested at the Gi phase and at the G2/M boundary (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hexamethylenebisacetamide (HMBA; ref. 19) was added to 4 mM and the mixture was incubated for 6 hr to arrest cells in G1. Flow cytometry of the HMBA-arrested cells, carried out with the Becton Dickinson Immunocytometry system, showed that -90%o of cells were in G1 phase.…”
Section: Methodsmentioning
confidence: 99%
“…An early manifestation of termination of cell division in MELC appears to be a transient prolongation of the GI phase of the cell cycle, which can be detected after cell transit through one complete S phase in the presence of inducer (8)(9)(10). After up to 4-5 terminal cell divisions, induced MELC are arrested in a GI-like phase of the cell cycle.…”
mentioning
confidence: 99%